SEMANGAT KENABIAN DALAM KITAB DANIEL DAN RELEVANSINYA BAGI PELAYANAN KATEKIS DI SEKOLAH - Leonard Sitepu; Agustinus Supriyadi (Lembaga Penelitian STKIP Widya Yuwana, 2019)
In the book of Daniel, there are nine prophetic values that can set as examples for catechists who work in the schools. Among them are: fa ith in God, praise and loving God, pray, Faithfull in service, doing a simple life in the midst of the luxury world, living in honest way, open to the media, had a wide view to the world, and optimism. The services of the catechists in schools can be said to be good so far. But there are still some of catechists who still find difficult to live in the prophetic values based on the Book of Daniel. This happens for many reasons. One of among the reasons is that there are some catechists still doubt for their own faith. Therefore, it is highly recommended that the catechists who work in the schools have to further explore and integrate the prophetic values as persisted in the Book of Daniel, especially the values related to the life of prayer, loyalty in service, honesty and openness to the media.